2013
DOI: 10.1021/jf4005862
|View full text |Cite
|
Sign up to set email alerts
|

Cassia Cinnamon as a Source of Coumarin in Cinnamon-Flavored Food and Food Supplements in the United States

Abstract: Coumarin as an additive or as a constituent of tonka beans or tonka extracts is banned from food in the United States due to its potentially adverse side effects. However, coumarin in food from other natural ingredients is not regulated. "True Cinnamon" refers to the dried inner bark of Cinnamomum verum. Other cinnamon species, C. cassia, C. loureiroi, and C. burmannii, commonly known as cassia, are also sold in the U.S. as cinnamon. In the present study, coumarin and other marker compounds were analyzed in au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(174 citation statements)
references
References 17 publications
(35 reference statements)
9
159
1
5
Order By: Relevance
“…[1][2][3] China is currently the largest exporter of cinnamon oil, and the abundant resources of cinnamon trees are mainly distributed in Southern China, especially the Guangxi Province, which accounts for over half of China's cinnamon oil exports. 4 Natural cinnamon oil contains a variety of chemical components, mainly including cinnamaldehyde (CA, 70-88%), o-methoxycinnamaldehyde (4-12%), cinnamyl acetate (CAc, 0.5-10%), and benzaldehyde (0.5-1%), and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] China is currently the largest exporter of cinnamon oil, and the abundant resources of cinnamon trees are mainly distributed in Southern China, especially the Guangxi Province, which accounts for over half of China's cinnamon oil exports. 4 Natural cinnamon oil contains a variety of chemical components, mainly including cinnamaldehyde (CA, 70-88%), o-methoxycinnamaldehyde (4-12%), cinnamyl acetate (CAc, 0.5-10%), and benzaldehyde (0.5-1%), and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Among sources of polyphenols, cinnamon may be of special interest since cinnamon and aqueous cinnamon extracts have been reported to be insulin sensitizers in vitro and in vivo (14). In general, cinnamon contains high levels of phenolic substances, including phenolic acids, coumarins, and proanthocyanidins (15). Several studies have suggested that cinnamon consumption has beneficial effects on human health, including antidiabetic effects, a hypoglycemic activity, and pancreas-protective effects (16), prevention of urinary tract infections (17), and neuroprotection, reduction of cardiovascular disease risk, and cancer prevention (13,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamomum cassia consists of a broad range of compounds such as cinnamaldehyde, cinnamic acid, cinnamyl alcohol, cinnamyl acetate, eugenol and to a large extent of coumarin (Wang et al 2013). Some of these compounds, particularly the volatile ones, can be separated and determined using GC-MS. High Performance Liquid Chromatography (HPLC) however is better technique to separate the more polar compounds present in Cinnamomum cassia which dissolves in water.…”
Section: Resultsmentioning
confidence: 99%